High‐performance bulk silicon interdigital capacitive temperature sensor based on graphene oxide. Issue 7 (1st March 2013) - Cai, Chun‐Hua; Qin, Ming
Abstract : A high‐performance bulk silicon interdigital capacitive temperature sensor based on graphene oxide (GO) is presented. Compared with typical CMOS integrated temperature sensors, the sensitivity of this bulk silicon interdigital capacitive temperature sensor was improved significantly by using GO as sensing material, and this temperature sensor can operate in the range of − 70 to 40°C.